New evaluated radioxenon decay data and its implications in nuclear explosion monitoring. (December 2018) - Galan, Monica; Kalinowski, Martin; Gheddou, Abdelhakim; Yamba, Kassoum
Abstract: This work presents the last updated evaluations of the nuclear and decay data of the four radioxenon isotopes of interest for the Comprehensive Nuclear-Test-Ban Treaty (CTBT): Xe-131 m, Xe-133, Xe-133 m and Xe-135. This includes the most recent measured values on the half-lives, gamma emission probabilities (Pγ) and internal conversion coefficients (ICC). The evaluation procedure has been made within the Decay Data Evaluation Project (DDEP) framework and using the latest available versions of nuclear and atomic data evaluation software tools and compilations. The consistency of the evaluations was confirmed by the very close result between the total available energy calculated with the present evaluated data and the tabulated Q-value. The article also analyzes the implications on the variation of the activity ratio calculations from radioxenon monitoring facilities depending on the nuclear database of reference. Highlights: New nuclear and decay data evaluations performed for the CTBT-relevant radioxenon isotopes Xe-131m, Xe-133, Xe-133m and Xe-135. Recommended evaluated nuclear and decay data are presented. Implications of evaluated data in nuclear explosion monitoring are demonstrated with regard to the zero time determination.